Private Tutoring Expenditure at Different levels of Education: An Explorative Analysis Using Case Study Approach - Laskar, Abdul Basith; Barbhuiya, Salma Khanam (International Journal of Psychosocial Rehabilitation, 2020)
Expenditure on education is considered as an important instrument in achieving sustainable development. Expenditure on education generally undertaken at institutional and household’s level. Private tutoring expenditure is considered to be a sizeable part of the household’s educational expenditure. According to Annual Status of Education Report (ASER), 2015 it is estimated that approximately one-fifth of rural Indian children in classes one to eight attend private tuition and spend on an average more than Rs. 2000 per annum to attend these tuition classes. It is important for policy-makers to consider tuition costs as a sizeable private cost of education which adversely can affect low-income house-holds’ demand for education. However, the evidence regarding the private tutoring expenditure at ground level is very limited in India in general and Hailakandi district in particular. Realising this urgency, this paper makes an attempt to understand the variation of private tuition expenditure based on different socio-demographic characteristics of students in Hailakandi district of Assam. The study uses primary data collected through field survey of 383 households in Hailakandi district. The study clearly reveals that per capita private tuition expenditure is more than Rs. 600 per month in a household of a student.